THE IMPLEMENTATION OF THE THEORY OF PLANNED BEHAVIOR AND RISK PROPENSITY TO MEASURE THE INVESTMENT INTENTION OF ACCOUNTING DEPARTMENT STUDENTS OF UNIVERSITAS BRAWIJAYA - Melati, Laras (Jurnal Ilmiah Mahasiswa FEB, 2020)
This research reports the effect of the implementation of theory of planned behavior and risk propensity on investment intention. The objects of this research are the accounting department students of Universitas Brawijaya, previously taking investment management and capital market subject. This qualitative research utilizes survey to collect data, resulting in 247 questionnaires to be analyzed by multiple linear regression method using SPSS software. The result indicates that attitudes, subjective norms, behavioral control perception, and risk propensity have positive effect on investment intention. This research is anticipated to promote students’ investment intention in capital markets and to be a reference for students in conducting research.    Keywords: attitudes, subjective norms, perception of behavioral control, risk propensity, investment intention.